2014
DOI: 10.1128/mcb.00999-13
|View full text |Cite
|
Sign up to set email alerts
|

Crumbs3 Is Essential for Proper Epithelial Development and Viability

Abstract: f First identified in Drosophila, the Crumbs (Crb) proteins are important in epithelial polarity, apical membrane formation, and tight junction (TJ) assembly. The conserved Crb intracellular region includes a FERM (band 4.1/ezrin/radixin/moesin) binding domain (FBD) whose mammalian binding partners are not well understood and a PDZ binding motif that interacts with mammalian Pals1 (protein associated with lin seven) (also known as MPP5). Pals1 binds Patj (Pals1-associated tight-junction protein), a multi-PDZ-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(141 citation statements)
references
References 58 publications
(74 reference statements)
14
120
0
3
Order By: Relevance
“…Moe forms a complex with Crb, actin and β-heavy spectrin (β Spectrin; Médina et al, 2002a), and has been shown to interact with Crb in tracheal morphogenesis (Kerman et al, 2008;Letizia et al, 2011). Furthermore, Crb3, a mouse Crb ortholog, has been shown to interact with ezrin (Ezr), a mammalian Moe ortholog, and Crb3-knockout mice display phenotypes similar to Ezr mutants (Whiteman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Moe forms a complex with Crb, actin and β-heavy spectrin (β Spectrin; Médina et al, 2002a), and has been shown to interact with Crb in tracheal morphogenesis (Kerman et al, 2008;Letizia et al, 2011). Furthermore, Crb3, a mouse Crb ortholog, has been shown to interact with ezrin (Ezr), a mammalian Moe ortholog, and Crb3-knockout mice display phenotypes similar to Ezr mutants (Whiteman et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ezrin is stabilized in its active conformation through phosphorylation at threonine 567 and binding to phosphatidylinositol 4,5-bisphosphate (PIP2) at the apical surface (Fehon et al, 2010;Jayasundar et al, 2012). Similarly, Crb3 is also required for proper elaboration of the brush border, as microvilli are shortened in Crb3 −/− mice, similar to Ezr −/− animals (Whiteman et al, 2014), although the underlying mechanisms are unclear.…”
Section: Formation Of the Microvillar Brush Bordermentioning
confidence: 97%
“…This process was thought to be defective in mice lacking the apical ezrin/radixin/moesin (ERM) protein ezrin, leading to the formation of isolated lumens and fused villi (Saotome et al, 2004). Loss of Crumbs3, another apical protein, causes a similar fusedvillus phenotype (Whiteman et al, 2014). However, more recent analyses, utilizing three-dimensional reconstruction to resolve luminal contiguity, have established that all luminal surfaces are connected during villus morphogenesis (Grosse et al, 2011).…”
Section: Expansion Of Apical Surface Does Not Occur Through Formationmentioning
confidence: 99%
“…In Drosophila embryos, loss of crb function results in embryonic lethality, caused by the breakdown of many epithelia (Grawe et al, 1996;Tepass, 1996;. Comparable phenotypes are observed in mouse embryos lacking Crb2 or Crb3, two of the three mammalian Crb genes (Charrier et al, 2015;Szymaniak et al, 2015;Whiteman et al, 2014;Xiao et al, 2011).…”
Section: Introductionmentioning
confidence: 99%